Building a Healthy Christian Family: Reflecting on the Story of Joseph in Community Service in Kupang City - Sihombing, Liston; Tampubolon, Jonris (English Lecturers and Teachers Association (ELTA), 2025)
The family as the smallest unit of the social environment of society, has an important role in shaping individual character. Kupang, located in East Nusa Tenggara, is a city with a majority Christian population. Instilling Christian values in families today is a common challenge amid the rise of technological developments and cultural exchanges. The purpose of this activity is to provide an understanding of Christian values such as love, honesty, and integrity as demonstrated by Joseph, one of the figures in the Bible. This community service activity involved 32 members of the Christian family who are members of the Sihombing Lumbantoruan clan association based in Kupang. The methodology used in this community service activity follows a qualitative approach with an interactive and participatory method. This activity lasted for 1 day and included material delivery and group discussions. The results of this activity showed that the participants had a deeper understanding of the values contained in the story of Joseph, such as patience, forgiveness, responsibility, and integrity. By understanding these values, the participants are expected to be able to apply them in their daily lives. Keywords: Christian Family, The Story of Joseph, Christian Values